2021
DOI: 10.1186/s12864-021-08019-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, genomic organization, and expression profiling of the CONSTANS-like (COL) gene family in petunia under multiple stresses

Abstract: Background CONSTANS-like (CO-like, COL) are putative zinc-finger transcription factors known to play vital role in various plant biological processes such as control of flowering time, regulation of plant growth and development and responses to stresses. However, no systematic analysis of COL family gene regarding the plant development and stress response has been previously performed in any solanaceous crop. In the present study, a comprehensive genome-wide analysis of COL family genes in petu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…In this study, we analyzed cis-elements in the 2000 bp promoter regions of MiCOL genes. These genes mainly included light, circadian control, hormone and stress-responsive elements and were similar to genes in the NtCOL gene family (Zhang et al, 2021), PaCOL gene family (Khatun et al, 2021) and PtCOL gene family (Li et al, 2020a). The results imply that MiCOL genes might be involved in light, circadian control, and hormone and stress response pathways in mango.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, we analyzed cis-elements in the 2000 bp promoter regions of MiCOL genes. These genes mainly included light, circadian control, hormone and stress-responsive elements and were similar to genes in the NtCOL gene family (Zhang et al, 2021), PaCOL gene family (Khatun et al, 2021) and PtCOL gene family (Li et al, 2020a). The results imply that MiCOL genes might be involved in light, circadian control, and hormone and stress response pathways in mango.…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that most of the MiCOL genes were mainly expressed in leaves and had high expression levels during the floral induction and differentiation periods. Similarly, 9 PtCOL genes are predominantly expressed in leaves (Li et al., 2020), 5 PaCOL genes are preferentially expressed in stems ( Khatun et al., 2021 ), and BnaCO. A10 and BnaCO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, MiCOL7A and MiCOL7B were expressed mainly in 20 DAF fruits, and MiCOL6 , MiCOL7A and MiCOL7B exhibited increased expression during the flowering induction and flowering of mango plants. In grape, nine PtCOL s were more highly expressed in leaves, while nine PaCOL genes were preferentially expressed in stems of Platanus acerifolia (Li et al, 2020; Khatun et al, 2021). In our previous study, MiCO , MiCOL1A , MiCOL16A and MiCOL16B were shown to be highly expressed in leaves and during flower‐forming induction and floral bud differentiation periods (Liu et al, 2020; Guo et al, 2022; Liu et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent loci on chromosomes 1A and 4D are related to two genes: CONSTANS-like and proteins abundant in late embryogenesis (LEA). The first is involved in various biological processes of plants, such as the control of the flowering time, regulation of growth and development, and responses to abiotic stress [32][33][34]. LEA proteins are recognized during the adaptation to abiotic stress, which includes dehydration, salinity, high temperature, and cold [35][36][37].…”
Section: Environmental Variables Involved In the Detection Of Adaptiv...mentioning
confidence: 99%